2019
DOI: 10.1177/1557085119842652
|View full text |Cite
|
Sign up to set email alerts
|

An International Study of the Contextual Effects of Gender Inequality on Intimate Partner Sexual Violence Against Women Students

Abstract: Rejecting biological and essentialist explanations, feminist scholars posit that gender inequality is a driving force behind sexual violence against women. Using an ecological approach, I test for significant associations between national-level gender inequality and intimate partner sexual violence (IPSV). I use multi-level generalized linear modeling to analyze the responses of 9,126 women from 29 countries in the International Dating Violence Study. I find that while controlling for other risk factors, gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
1
9
1
Order By: Relevance
“…As for gender equality attitudes, we found that people with more gender equitable attitudes presented more awareness, more proactive attitudes, less tolerance, as well as broader definition of serious violence behaviors. A similar relationship has been found between gender equality attitudes and prevalence of IPVAW in previous studies (e.g., Grabe et al, 2015;Heise & Kotsadam, 2015;Lasley & Durtschj, 2016;LeSuer, 2019;Zapata-Calvente et al, 2019). Stalans and Finn (2006) further uncovered that people who disfavor male-dominant relationships are more likely to believe that husbands' use of violence is intentional and unjustifiable.…”
Section: Discussionsupporting
confidence: 81%
“…As for gender equality attitudes, we found that people with more gender equitable attitudes presented more awareness, more proactive attitudes, less tolerance, as well as broader definition of serious violence behaviors. A similar relationship has been found between gender equality attitudes and prevalence of IPVAW in previous studies (e.g., Grabe et al, 2015;Heise & Kotsadam, 2015;Lasley & Durtschj, 2016;LeSuer, 2019;Zapata-Calvente et al, 2019). Stalans and Finn (2006) further uncovered that people who disfavor male-dominant relationships are more likely to believe that husbands' use of violence is intentional and unjustifiable.…”
Section: Discussionsupporting
confidence: 81%
“…Hudson (2009) stresses caution in this area, but comments "overall, the security framework does seem to have some positive impacts for women's rights activism" by providing political space and opportunity (p. 66). Following scholars that have argued for a structurally driven investigation of campus sexual violence that considers the systematic issues of gender and power (Khan et al, 2020;LeSuer, 2020;Moylan & Javorka, 2020), expanding campus sexual violence past acts of interpersonal violence that are isolated events into the realm of everyday terrorism that is upheld by politically and economically motivated institutions is needed.…”
Section: Everyday Terrorism: a Feminist/critical Perspective On Securitymentioning
confidence: 99%
“…Scholars have examined the association between violence and the amelioration hypothesis. LeSuer (2020) examined the International Dating Violence Survey for 29 countries. The findings demonstrated that intimate partner sexual violence was more likely to occur in countries with more gender inequality.…”
Section: Theoretical Frameworkmentioning
confidence: 99%